Currency Crises And Economic Growth Of Emerging Countries: An Analysis For Turkish Economy In 1970-2017 - Tchikou, Faouzi; Belhia, Yamina (University of eloued - جامعة الوادي, 2018)
The main purpose of this research paper is to identify the effect of currency crises on economic growth in the emerging Turkish economy. The objective of present study is to empirically examine the short-run and the long run relation between currency crisis and economic growth condition in turkey over the period from 1970 -2017, by employing the autoregressive distributive lag (ARDL) modelling technique based on Pesaran et al. (2001). The selected period is important, because it represents the crucial time for Turkish economy, this explains his affected by too many economic phenomena. This research work is one of the very few studies that have investigated Influence the currency crisis on long run economic growth in turkey country situation using ARDL model. Moreover, it contributes to the existing literature in the area.
مقال
Keywords: currency crises, GDP Growth, impulse function, Turkish economy, Autoregressive Distributed Lag (ARDL).